IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR FISIKA - Yuniati, Ni Nyoman (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2018)
This research was conducted at SMA Negeri 1 Denpasar in class XI Science 8 academic year 2014/2015,which the ability of learners regarding the particle dynamics material is quite low.The purpose of writing this class action research is to determine whether the model of Problem Based Learning can improve the performance of learners.Method of data collection is learning achievement test and student activity. The method of data analysis is using Descriptive method for qualitative data and quantitative data.The results which are obtained from this research are the Problem Based Learning can improve the performance of learners. This evident isfound from the results obtained before using Problem Based Learning method reached an average value of 63.25. But the result in the first cycle of using the method reached an average value of 79.51 and the second cycle reached an average value of 85.00.The conclusion from this study is the model of Problem Based Learning can improve learning achievement Physics Newton's laws of matter About Gravity.